Uji Infektifitas dan Efektifitas Rhizobia sp. terhadap Tanaman Kedelai di Rumah Kasa pada Tanah Ultisol dengan pH yang Berbeda - M. Reza Alfikri; Hardy Guchi; Asmarlaili Sahar Hanafiah (Jurnal Pertanian Tropik, 2018)
Rhizobia fixed nitrogen from the air and supplied legume and effected to soil fertility. The research was conducted in May 2017 until November at Soil Biology Laboratory and Screen House of Agriculture Faculty University of Sumatera Utara. This research was carried out with 2 stages: growth test at various pH with isolate tested (TJA 1, TJA 2, TJA 3, BGR 1, BGR 2, BGR 3, BGR 4, BALAI 1, BALAI 2, BALAI 3, LP 1, LP 2, LP 3, LP 4 and LAB) and the infectivity test and the effectivity of Rhizobia. The research used Randomized Block Design with 2 treatment: Lime (Without Lime and Lime 1 x Aldd) and Isolate Rhizobia (TJA 1, TJA 3, BGR 1, BGR 3, BGR 4, BALAI 2, BALAI 3, LP 1, LP 2, LP 4 and LAB). The application of Rhizobia’s isolate BGR 3 showed the infektively with root nodule amount criteria(124,00). The isolate Rhizobia’s BGR 3 effectively increased N plant level and N absorption (3,80 %; 31,08mg/plant). Application of isolate Rhizobia was not able to increase the level of P plants and P plant uptake. The best interaction was shown (Plant height 85.00 cm, stem diameter 3.93 mm, root nodule 127.50, N level of 3.80%, N absorption 30.16 mg / plant) by treatment of BGR 3 and Lime 1 x Aldd.